1998
DOI: 10.1002/(sici)1096-9098(199806)68:2<70::aid-jso2>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

On the holistic approach in cellular and cancer biology: Nonlinearity, complexity, and quasi-determinism of the dynamic cellular network

Abstract: A keystone of the molecular reductionist approach to cellular biology is a specific deductive strategy relating genotype to phenotype—two distinct categories. This relationship is based on the assumption that the intermediary cellular network of actively transcribed genes and their regulatory elements is deterministic (i.e., a link between expression of a gene and a phenotypic trait can always be identified, and evolution of the network in time is predetermined). However, experimental data suggest that the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 64 publications
3
39
0
1
Order By: Relevance
“…The possibility of mapping the experimental Gompertz curve, characterizing the Brown-Pearce tumor growth, onto the fractal power-law scaling function confirms that Gompertzian growth is a self-similar and allometric process (Bajzer, 1999) of a holistic nature (Waliszewski et al, 1998;Molski and Konarski, 2003). It means that all spatially separated sublements (cells) of the whole system (tumor) are interrelated via long-range (slowly decaying) interactions, which seem to be an essential ingredient of the self-organized Gompertzian growth (Mombach et al, 2002).…”
Section: Resultsmentioning
confidence: 71%
“…The possibility of mapping the experimental Gompertz curve, characterizing the Brown-Pearce tumor growth, onto the fractal power-law scaling function confirms that Gompertzian growth is a self-similar and allometric process (Bajzer, 1999) of a holistic nature (Waliszewski et al, 1998;Molski and Konarski, 2003). It means that all spatially separated sublements (cells) of the whole system (tumor) are interrelated via long-range (slowly decaying) interactions, which seem to be an essential ingredient of the self-organized Gompertzian growth (Mombach et al, 2002).…”
Section: Resultsmentioning
confidence: 71%
“…This variable is well established in the fields of pathology and cancer biology (36). Indeed, it has been suggested that altered fractal dimension is one of the earliest events in colon carcinogenesis (37). Whereas fractal dimension assesses tissue organization at the cellular to the large organelle level, spectral slope is affected by much smaller structures (small organelles to macromolecular complexes).…”
Section: Discussionmentioning
confidence: 99%
“…They tend to be quasi (almost but not quite)-periodic, the periodicities are a complex of many periods, and they can swing between different quasi-periodic states. But they are not at all random (Waliszewski et al, 1998;Marino et al, 2000Marino et al, ,2009. Living systems are organized such that they manifest operational features ascribed to hierarchical and heterarchical structures from quantum to organism levels (Dirks, 2008).…”
Section: The Influence Of Spatially Inhomogeneous Electromagnetic Fiementioning
confidence: 99%